Thymic and extrathymic Aire‐expressing cells in maternal‐fetal tolerance. Issue 1 (10th May 2022) - Sun, Im‐Hong; Gillis‐Buck, Eva; Mackenzie, Tippi C.; Gardner, James M.
Abstract: Healthy pregnancy requires maternal immune tolerance to both fetal and placental tissues which contain a range of self‐ and non‐self‐antigens. While many of the components and mechanisms of maternal‐fetal tolerance have been investigated in detail and previously and thoroughly reviewed (Erlebacher A. Annu Rev Immunol . 2013;31 :387–411), the role of autoimmune regulator ( Aire ), a critical regulator of central tolerance expressed by medullary thymic epithelial cells (mTECs), has been less explored. Aire is known to facilitate the expression of a range of otherwise tissue‐specific antigens (TSAs) in mTECs, and here we highlight recent work showing a role for mTEC‐mediated thymic selection in maintaining maternal‐fetal tolerance. Recently, however, our group and others have identified additional populations of extrathymic Aire‐expressing cells (eTACs) in the secondary lymphoid organs. These hematopoietic antigen‐presenting cells possess the ability to induce functional inactivation and/or deletion of cognate T cells, and deletion of maternal eTACs during pregnancy increases T‐cell activation in the lymph nodes and lymphocytic infiltration of the uterus, leading to pregnancy complications including intrauterine growth restriction (IUGR) and fetal resorption. In this review, we briefly summarize findings related to essential Aire biology, discuss the known roles of Aire‐deficiency related to pregnancy complications and infertility, review the newly discovered role for eTACs in the maintenance of maternal‐fetal tolerance—as well as recent work defining eTACs at the single‐cell level—and postulate potential mechanisms by which eTACs may regulate this process.